The real consequences of macroprudential FX regulations - Hyeyoon Jung (Federal Reserve Bank of New York, 2021)
I exploit a natural experiment in South Korea to examine the real effects of macroprudential foreign exchange (FX) regulations designed to reduce risk-taking by financial intermediaries. By using crossbank variation in the regulation's tightness, I show that it causes a reduction in the supply of FX derivatives (FXD) and results in a substantial decline in exports for the firms that were heavily relying on FXD hedging. I offer a mechanism in which imbalances in hedging demand, banks' costly equity financing, and firms' costly switching of banking relationships play a central role in explaining the empirical findings.
Keywords: E44; F31; G15; G28; G32; 330; real effects; macroprudential policy; international finance; derivatives hedging; FX risk management